The Impact of Uncapping of Mandatory Retirement on Postsecondary Institutions. (August 2013) - Weinberg, Sharon L.; Scott, Marc A.
The Federal Age Discrimination in Employment Act passed by Congress in 1986 eliminated mandatory age-related retirement at age 70. Initially, all postsecondary institutions were exempt from the Act. Based on a report by the National Research Council (NRC), which forecast only a minimal impact of this Act on higher education, the federal government allowed the exemption to lapse; effective December 31, 1993, faculty would no longer be subject to mandatory retirement for age. Our results of an empirical analysis on nearly four decades of faculty data (from 1981 to 2009) from a large private metropolitan research university in the northeast contradicts that forecast and shows the extent to which faculty retirement behavior has changed following the enactment of the Act and the lapse of the exemption for higher education faculty. Although only 11% of faculty who were subject to mandatory retirement remained after age 70 (perhaps those with special arrangements), we find after the law changed that 60% of faculty no longer subject to mandatory retirement are expected to remain employed beyond age 70 and 15% will retire at age 80 or over. This is a dramatic shift in retirement behavior, one that was not forecast by the NRC committee. Our results also show how many years after the prior mandatory retirement age of 70, faculty now remain at their institutions. We also offer suggestions as to some of the potential reasons (consistent with the literature) why, since the change in the law, some faculty wait longer than others to retire, but we do so primarily to spur discourse, as these factors are based on our understanding of this institution. Our findings are limited to this single institution and do not imply a general trend for all postsecondary institutions. Additional studies are recommended to determine whether uncapping has had a similar effect at other postsecondary institutions.